13.9k views
0 votes
Please show step by step need it now

Please show step by step need it now-example-1
User Wizart
by
5.0k points

1 Answer

5 votes

Answer:

x = 6+3y

y = y (any number)

the rest should follow the same steps

Explanation:

2x-6y=12 -> divide both sides by 2 (GCF)

x-3y = 6 -> solve for x, because it has 1 as its coefficient, or the lowest coefficent

x = 6+3y

-5x+15y=-30 -> divide both sides by 5

-1x+3y=-6 -> plug in x from previous equation

-(6+3y) + 3y = -6

-6-3y+3y = -6

y = y

User Shashika Virajh
by
5.1k points